Baby booming inequality? Demographic change and earnings inequality in Norway, 1967-2000 - Ingvild Almås; Tarjei Havnes; Magne Mogstad (Center for Economic Studies and ifo Institute (CESifo), 2010)
In this paper, we demonstrate how age-adjusted inequality measures can be used to evaluate whether changes in inequality over time are due to changes in the age structure. To this end, we use administrative data on earnings for every male Norwegian during 1967-2000. We find that the substantial rise in earnings inequality over the 1980s and into the early 1990s, is to some extent driven by the fact that the large baby boom cohorts are approaching the peak of the age-earnings profile. We further demonstrate that the impact of age adjustments on the trend in inequality during the period from 1993-2000 is highly sensitive to the method used: while the most widely used age-adjusted inequality measure indicates little change in inequality over this period, a new and improved age-adjusted measure suggests a decline in inequality.
Keywords: D31; D63; D91; E21; 330; inequality trend; age structure; age-earnings profile; Gini coefficient; Einkommensverteilung; Soziale Ungleichheit; Altersstruktur der Bevölkerung; Gini-Koeffizient; Männer; Norwegen